Age and Gender Peculiarities of Bone Mineral Density in Children from Donetsk Region - F.V. Klymovytsky; V.V. Povoroznyuk (Zaslavsky O.Yu., 2013)
Using dual-energy densitometer Discovery QPR (Bedford, USA) there had been examined 168 children from of one of comprehensive schools of Donetsk. Parameters of bone mineral density at the lumbar spine, proximal femur and the entire skeleton had been studied, that for the first time made it possible to create reference database of children and adolescents. It has been proved also that age has significant impact on variability of bone mineral density indices. It is found that the critical period for the formation of peak bone mass in girls is the age of 10-15 years, in boys - 12-15 years.